Yazı Tasarımını Önemseyen ve Sahip Çıkan Bir Kuşağın Temsilcisi: Mustafa Eren - Yıldırım, Dicle (Anadolu Üniversitesi, 2020)
Bu çalışma; Mustafa Eren’in tasarımcı kimliğini ve görünürlüğünü temel alarak, Eren’i sanat ve tasarım aksında incelemeyi amaçlamıştır. Makalenin hedefi; Mustafa Eren’in tasarım eğitimi, profesyonel yaşamı, özellikle de yazı tasarımı ve kaligrafi çalışmalarını kapsamlı bir biçimde aktarmak; mevcut bilinirliğinin ötesine geçerek onu daha iyi tanıtmak, anlatmak ve hatırlatmaktır. Çalışmada, Eren ile bir dönemin nabzını tutan birebir görüşmeler ve röportajlar gerçekleştirilmiş; grafik tasarım alanında geçmişten bugüne yetkin olan isimlerden dinlenip Eren’e farklı açılardan bakılması sağlanmaya çalışılmıştır. Elde edilen bilgiler, araştırmalar ve ortaya çıkan değerlendirmeler ile birlikte Mustafa Eren hakkında tasarım tarihine detaylı bir not düşülmüştür. Tasarımcı kimliğinin sadece zaman ve mekâna sıkışmayan ölçekte bir üretim alanı olduğu gözler önüne serilmiş, geniş bir perspektifte ele alınmıştır. Araştırmanın sonucunda; tasarımcının geçmişten günümüze üretimleri dönemsel altyapıları irdelenmiş ve değerlendirilmiştir. Bu değerlendirme üzerine, Mustafa Eren’in yazı tasarımları ve kaligrafik düzenlemeleriyle tipografiye sağladığı katkılar ortaya konmuştur.

This study aims to assess Mustafa Eren in the art and design axis based on his designer identity and visibility. The goal of the article is to convey Mustafa Eren’s design education, professional life, and especially his typeface design and calligraphy works comprehensively, to better introduce him by going beyond his current recognition, explain and remind him. In the study, one-to-one meetings and interviews were held with Eren, which kept fingers on the pulse of an era, competent names from the past to present in the field of graphic design were listened to, and views of Eren from different perspectives were trialed. With the obtained information, the research and emerging evaluations, a detailed note has been recorded about Mustafa Eren in the history of graphic design. It has been revealed and discussed in a broad perspective that his designer identity is a production area that does not get stuck in only time and space. As a result of the research, the periodic infrastructures of the designer’s past to present productions were examined and evaluated. Upon this evaluation, Mustafa Eren’s contributions to typography with his writing designs and calligraphic arrangements were revealed.
Representative of a Generation That Minded and Adopted Typeface Desing: Mustafa Eren
Keywords: Grafik Tasarım; Yazı Tasarımı; Tipografi; Kaligrafi; Graphic Design; Typeface Design; Typography; Design; Calligraphy